ER stress and/or ER-phagy in drug resistance? Three coincidences are proof - Sameer Kumar Panda; Ibone Rubio Sanchez-Pajares; Ayesha Rehman; Vitale Del Vecchio; Luigi Mele; Sandhya Chipurupalli; Nirmal Robinson; Vincenzo Desiderio (Cell Communication and Signaling)
Abstract Cancer is influenced by the tumor microenvironment (TME), which includes factors such as pH, hypoxia, immune cells, and blood vessels. These factors affect cancer cell growth and behavior. The tumor microenvironment triggers adaptive responses such as endoplasmic reticulum (ER) stress, unfolded protein response (UPR), and autophagy, posing a challenge to cancer treatment. The UPR aims to restore ER homeostasis by involving key regulators inositol-requiring enzyme-1(IRE1), PKR-like ER kinase (PERK), and activating transcription factor 6 (ATF6). Additionally, ER-phagy, a selective form of autophagy, eliminates ER components under stress conditions. Understanding the interplay between hypoxia, ER stress, UPR, and autophagy in the tumor microenvironment is crucial for developing effective cancer therapies to overcome drug resistance. Targeting the components of the UPR and modulating ER-phagy could potentially improve the efficacy of existing cancer therapies. Future research should define the conditions under which ER stress responses and ER-phagy act as pro-survival versus pro-death mechanisms and develop precise methods to quantify ER-phagic flux in tumor cells.